NUCLEAR ORIENTATION AND COINCIDENCE STUDIES OF I-118 AND CS-118 ISOTOPES - Shaw, T; Green, V; Stone, N; Walker, P; Hamilton, W; Collins, S; Grant, I; Rikovska, J (Baltzer Science Publishers, Baarn/Kluwer Academic Publishers, 1985)
Gamma-gamma coincidence and on-line nuclear orientation experiments have been done on118Ig(2-),118Im(7-),118Csg(2-) and118Csm(8-). The activities were produced by 175 MeV32,34S beams on93Nb and the products passed through an isotope separator. Nuclear moments for the118I isomers are deduced. The decay scheme of118Te is given and various spin assignments made, particularly 1944.3 KeV (3-) and 957.3 KeV (o+). Equilibrium distortion of the118I ground state is discussed briefly. © 1985 J.C. Baltzer A.G., Scientific Publishing Company.